The nature and likely redshift of GLEAM J0917–0012. (21st September 2021) - Drouart, Guillaume; Seymour, Nick; Broderick, Jess W.; Afonso, José; Chhetri, Rajan; De Breuck, Carlos; Emonts, Bjorn; Galvin, Tim J.; Lehnert, Matthew D.; Morgan, John; Stern, Daniel; Vernet, Joël; et al.
Abstract: We previously reported a putative detection of a radio galaxy at $z=10.15$, selected from the GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey. The redshift of this source, GLEAM J0917–0012, was based on three weakly detected molecular emission lines observed with the Atacama Large Millimetre Array (ALMA). In order to confirm this result, we conducted deep spectroscopic follow-up observations with ALMA and the Karl Jansky Very Large Array (VLA). The ALMA observations targeted the same CO lines previously reported in Band 3 (84–115 GHz) and the VLA targeted the CO(4-3) and [CI(1-0)] lines for an independent confirmation in Q -band (41 and 44 GHz). Neither observation detected any emission lines, removing support for our original interpretation. Adding publicly available optical data from the Hyper Suprime-Cam survey, Widefield Infrared Survey Explorer ( WISE ), and Herschel Space Observatory in the infrared, as well as $<$ 10 GHz polarisation and 162 MHz inter-planetary scintillation observations, we model the physical and observational characteristics of GLEAM J0917–0012 as a function of redshift. Comparing these predictions and observational relations to the data, we are able to constrain its nature and distance. We argue that if GLEAM J0917–0012 is at $z<3, $ then it has an extremely unusual nature, and that the more likely solution is that the source lies above $z=7$ .